Case report: SLC6A1 mutations presenting with isolated absence seizures: description of 2 novel cases - Caputo, Davide; Franceschetti, Silvana; Castellotti, Barbara; Freri, Elena; Zorzi, G.; Saletti, Veronica; Canafoglia, Laura; Granata, Tiziana (Frontiers in Neuroscience, 2023)
We report the clinical and EEG data of two patients harboring heterozygous SLC6A1 mutations, who presented with typical absence seizures at 3 Hz spike and wave as well as with mild cognitive disability. Neuroradiological and other laboratory investigations were normal. Our observations suggest that SLC6A1 mutations can be suspected in children with typical absences as the only seizure type, especially if associated with, even mild, cognitive deficits.